Assessing the impact of Youth-in-Agribusiness Program on poverty and vulnerability to poverty in Nigeria - Bello, L.O.; Baiyegunhi, L.J.; Danso-Abbeam, Gideon; Ogunniyi, A.I.; Abdoulaye, Tahirou; Manyong, Victor; Bamba, Z.; Awotide, B.A. (MDPI, 2022)
Poverty persists in many developing countries, including Nigeria, owing to inadequate infrastructure, unemployment, or poor working conditions, among other factors. Youth poverty and vulnerability to poverty have been identified to prevalent among the young population. Using an endogenous switching probit regression approach, in this study, we evaluated the impacts of youth participation in agribusiness programs (YIAPs) on poverty and vulnerability to poverty in Nigeria. Our findings revealed that some demographic and institutional factors significantly influence poverty and vulnerability to poverty among youth. The impact estimates indicate that participation in an agribusiness program has a significant positive effect on poverty reduction among youth. Moreover, there would have been about a 28% reduction in exposure to future poverty for non-participants had they participated in a YIAP. Our results suggest that intervention programs, such as YIAPs, that focus on skill acquisition and youth empowerment should be strengthened and scaled-up in order to improve youth welfare and subsequently reduce/eradicate poverty and vulnerability to poverty among youth.